Relationship Between The Level of Knowledge about Diabetes and The Willingness of Family Members to Provide Support for Patients with Diabetes Mellitus - Bambang Sarwono; Siti Apriyanti; Heru Supriyatno; Nita Tri Septiana (Midwifery and Nursing Research, 2026)
Background: Type 2 Diabetes Mellitus is a complex global health issue that can lead to serious complications if not managed properly. The role of family members in assisting diabetes patients is crucial for improving treatment adherence and quality of life. However, the willingness of family members to provide such support is often influenced by their level of knowledge regarding the disease. This study aims to determine the relationship between the knowledge level of family members about Type 2 Diabetes Mellitus and their willingness to provide assistance to patients. Methods: This study utilized a quantitative approach with a cross-sectional design. The research sample consisted of 66 family members of patients with Type 2 Diabetes Mellitus in Sumberarum Village, Magelang Regency, selected using a purposive sampling technique. Data were collected using the Diabetes Knowledge Questionnaire-24 and a questionnaire measuring the level of willingness to provide assistance. Data analysis was performed using the Spearman correlation test. Results: The results of this study indicated that the majority of respondents were aged 25-44 years, male, had a secondary level of education, were employed, and had family members who had suffered from diabetes for more than one year. This study found that the majority had a moderate level of knowledge (62.1%) and a high level of willingness to provide assistance (57.6%). The Spearman correlation test results showed a significant positive relationship between the level of knowledge and the willingness to provide assistance (correlation coefficient = 0.713; p = 0.000). Conclusion: The results of the study indicate a strong relationship between the level of knowledge and the willingness of family members to provide support for diabetes patients. Future research is expected to conduct studies that implement interventions to improve both the knowledge and willingness of family members to assist diabetes patients.